The shed P2X7 receptor is an index of adverse clinical outcome in COVID-19 patients - Vultaggio-Poma, Valentina; Sanz, Juana Maria; Amico, Andrea; Violi, Alessandra; Ghisellini, Sara; Pizzicotti, Stefano; Passaro, Angelina; Papi, Alberto; Libanore, Marco; Di Virgilio, Francesco; Giuliani, Anna Lisa (Frontiers in Immunology, 2023)
Introduction The pathophysiology of the Corona Virus Disease 2019 (COVID-19) is incompletely known. A robust inflammatory response caused by viral replication is a main cause of the acute lung and multiorgan injury observed in critical patients. Inflammasomes are likely players in COVID-19 pathogenesis. The P2X7 receptor (P2X7R), a plasma membrane ATP-gated ion channel, is a main activator of the NLRP3 inflammasome, of the ensuing release of inflammatory cytokines and of cell death by pyroptosis. The P2X7R has been implicated in COVID-19-dependent hyperinflammation and in the associated multiorgan damage. Shed P2X7R (sP2X7R) and shed NLRP3 (sNLRP3) have been detected in plasma and other body fluids, especially during infection and inflammation. Methods Blood samples from 96 patients with confirmed SARS-CoV-2 infection with various degrees of disease severity were tested at the time of diagnosis at hospital admission. Standard haematological parameters and IL-6, IL-10, IL-1β, sP2X7R and sNLRP3 levels were measured, compared to reference values, statistically validated, and correlated to clinical outcome. Results Most COVID-19 patients included in this study had lymphopenia, eosinopenia, neutrophilia, increased inflammatory and coagulation indexes, and augmented sNLRP3, IL-6 and IL-10 levels. Blood concentration of sP2X7R was also increased, and significantly positively correlated with lymphopenia, procalcitonin (PCT), IL-10, and alanine transaminase (ALT). Patients with increased sP2X7R levels at diagnosis also showed fever and respiratory symptoms, were more often transferred to Pneumology division, required mechanical ventilation, and had a higher likelihood to die during hospitalization. Conclusion Blood sP2X7R was elevated in the early phases of COVID-19 and predicted an adverse clinical outcome. It is suggested that sP2X7R might be a useful marker of disease progression.